Research On Raspberry Pi 3b+ For Load Balancing On 2 Web Servers - Noor, Alfarabi Ivandi; Hertiana , Sofia Naning; Irawan, Arif Indra (eProceedings of Engineering, 2024)
Augmenting the web server's capacity may leadto system failures or excessive load, ultimately resulting inserver downtime. In order to address this issue, a loadbalancing strategy is employed. This technique involves thedistribution of incoming requests over multiple serverssimultaneously, thereby reducing the workload absorbed byeach individual server. The scalability of the system enablesthe equitable distribution of server traffic loads acrossnumerous connection lines, optimizing throughput,enhancing reaction time, and mitigating the risk of overloadon any single connection line. The Nginx load balancerprogram will be utilized, employing the Round Robin andLeast Connection algorithms. These methods will beconnected to two Django web servers. In the analysis of theThroughput, Delay, and Response time metrics for the twoalgorithms, it was observed that there were no statisticallysignificant differences, with the exception of the testsconducted with 5000 and 6000 requests. Therefore, it can beinferred that the utilization of Round-Robin and LeastConnection algorithms is appropriate for a websiteexperiencing traffic volumes ranging from 500 to 4000requests per minute, with content sizes that are notexcessively large, in order to prevent any potential issuesduring the server load sharing procedure. Keywords — Raspberry Pi 3B+, Load Balancing, Nginx, Django, Round Robin, Least Connection.